1984
DOI: 10.1159/000199009
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Lysophospholipase and Increased Phospholipase A<sub>2 </sub>Activity in Heal Mucosa from Patients with Crohn’s Disease

Abstract: Lysophospholipase (EC 3.1.1.5) and phospholipase A2 (EC 3.1.1.4) were determined in ileal mucosa from patients with Crohn’s disease (CD) and non-inflammatory bowel diseases (NIBD). In addition, the activities of alkaline phosphatase, sucrase, maltase, and lactase were determined. The lysophospholipase activity, like that of alkaline phosphatase, sucrase and maltase, was decreased in affected areas of CD, whereas the phospholipase A2 activity was rather increased. Lysophospholipase and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In a previous study, based on a small number of patients, we found increased phospholipase A2 (EC 3.1.1.4) activity in surgical specimens of severely inflamed ileal mucosa in some cases of Crohn's disease [ 14], The increase, however, was not statisti cally greater than in ileal specimens from patients operated on for carcinoma of the colon.…”
mentioning
confidence: 63%
“…In a previous study, based on a small number of patients, we found increased phospholipase A2 (EC 3.1.1.4) activity in surgical specimens of severely inflamed ileal mucosa in some cases of Crohn's disease [ 14], The increase, however, was not statisti cally greater than in ileal specimens from patients operated on for carcinoma of the colon.…”
mentioning
confidence: 63%
“…We previously reported increased permeability of inflamed ileal seg ments in Crohn's disease [1], We also found enhanced phospholipase A2 activity in the ileal mucosa of patients with previous resec tion for Crohn's ileitis whether or not there was recurrent inflammation [2,3]. The pos sibility of a relationship between inflamma tion, phospholipase A2 activity and perme ability of intestinal mucosa in inflammatory bowel disease, though intriguing, does not seem to have been hitherto investigated.…”
mentioning
confidence: 76%
“…On the other hand, it remains entirely unclear whether decreased en zyme activity underlies or is due to the disease process. Moreover, there is no reason to believe that the decrease in PAF acetylhydrolase is specific, because previous studies have shown that in the intestinal mucosa of patients with Crohn's disease the activities of a number of different enzymes are lower [36,38]. In addition, the activity of PAF acetylhydrolase in intestinal mucosa during other inflam matory disorders of the bowel remains to be investigated in order to test whether the changes are disease specific.…”
Section: Discussionmentioning
confidence: 99%